2002
DOI: 10.1136/gut.51.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Association between severity of type A hepatitis and nucleotide variations in the 5` non-translated region of hepatitis A virus RNA: strains from fulminant hepatitis have fewer nucleotide substitutions

Abstract: Background: Type A hepatitis is still a considerable problem in both underdeveloped and developed countries. Why some patients progress to fulminant type A hepatitis and others do not is unclear. Aims: To determine if nucleotide differences in the genome of hepatitis A virus (HAV) are responsible for the range of clinical severities, we analysed the 5′ non-translated region (5′NTR) of the HAV genome, which has an internal ribosomal entry site and is important for cap independent translation of the viral messag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(98 citation statements)
references
References 29 publications
2
94
1
1
Order By: Relevance
“…On the other hand, increased disease severity may be associated with viral factors, such as genotype and nucleotide changes in, for example the 5 0 -nontranslated-region of the virus [Fujiwara et al, 2002]. No indication was found in this study that genotype influenced duration of jaundice or HAV excretion, nor did other studies looking for an association between HAV genotype and disease severity [Fujiwara et al, 2003;Rezende et al, 2003;Normann et al, 2004].…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, increased disease severity may be associated with viral factors, such as genotype and nucleotide changes in, for example the 5 0 -nontranslated-region of the virus [Fujiwara et al, 2002]. No indication was found in this study that genotype influenced duration of jaundice or HAV excretion, nor did other studies looking for an association between HAV genotype and disease severity [Fujiwara et al, 2003;Rezende et al, 2003;Normann et al, 2004].…”
Section: Discussioncontrasting
confidence: 64%
“…The deletion found in the present study had never been identified in HAV isolates and therefore we could not predict an alteration in secondary structure or HAV translation. Fujiwara et al (12) reported a possible association between the severity of type A hepatitis and nucleotide substitutions in the middle part of 5'NTR. However, in our study the presence or absence of symptoms was not associated with the mutations in this part of genome.…”
Section: Vp1 2amentioning
confidence: 99%
“…Recently, it was demonstrated that the central part of the 5' non-translated region (5'NTR) of HAV might be correlated with the severity of HAV infection (11,12). In order to study the variability of the nucleotide sequence in both regions of the HAV genome and to identify the genotypes circulating in the Northeast region of Brazil, direct nucleotide sequencing and phylogenetic analysis were performed on HAV strains obtained from patients reported to the Public …”
Section: Introductionmentioning
confidence: 99%
“…Among these viral factors it may be pointed that some mutations at the 5'NCR of HAV or at the VP1X2A and 2C regions have been associated with fulminant hepatitis (Fujiwara et al, 2002;Fujiwara et al, 2001;Fujiwara et al, 2003) or higher virulence in tamarinds (Emerson et al, 2002), respectively. However, there is no consensus whether the VP1X2A-derived genotypes are clinically different, although some strains belonging to the former genotype VII now included in genotype II were associated with fulminant cases (Ching et al, 2002;Costa-Mattioli et al, 2002;Mackiewicz et al, 2010).…”
Section: Hepatitis a Virus (Hav)mentioning
confidence: 99%